Simplesmente igreja : um olhar sobre inclusão de pessoas com deficiência em busca de contribuições para uma práxis comunitária inclusiva - Tehzy, Sandra Kamien (2008)
This paper surveys the inclusion of people with disabilities within the Evangelical Church of Lutheran Confession in Brazil (ECLCB) based on the dialogue between two fields of knowledge, religion and education. They study discusses the relation between church and inclusion, examining issues raised by debates in the educational field in dialogue with congregational "voices", statements collected in interviews with leaders of congregations and with members of coordinating committees working with disabled people at the synod and national levels. The first chapter briefly presents the history of ECLCB, from its origins to the present, highlighting the development of the reflection and the effort to include disabled people within the church. The second chapter provides a historical, biblical-theological review, in an attempt to discern how people with disabilities were seen and understood in pre-Christian times. The third chapter looks for contributions towards an inclusive congregational practice by means of a dialogue in line with the Pauline image of the church as a "body" between the issues and reflections on inclusion in the educational field and the congregational day to day expressed in the statements made by the people interviewed.